The places of modernity in early Mexican American literature, 1848-1948 - Aranda, José F., 1961- (University of Nebraska Press, 2022)
José F. Aranda Jr. demonstrates how the burdens of modernity become the dominant discursive logic for understanding why people of Mexican descent nonetheless wrote and invested in print culture without any guarantee of its social, cultural, or political efficacy.
Keywords: Mexican Americans -- Intellectual life.; Modernism (Literature); American literature -- 20th century -- History and criticism.; American literature -- 19th century -- History and criticism.; American literature -- Mexican American authors -- History and criticism.; Américains d'origine mexicaine -- Vie intellectuelle.; Modernisme (Littérature); Littérature américaine -- 20e siècle -- Histoire et critique.; Littérature américaine -- 19e siècle -- Histoire et critique.; Littérature américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique.; LITERARY CRITICISM / American / Hispanic & Latino.; LITERARY CRITICISM / American / Hispanic American; Mexican Americans -- Intellectual life; American literature -- Mexican American authors; American literature; 1800-1999; Electronic books.; Literary criticism; Criticism, interpretation, etc.; Literary criticism.; Critiques littéraires.